Economic dependence of the consumer on the feasibility to regulate the heat supply system (Academic journal Industrial Machine Building Civil Engineering, 2022)
The paper explore the issue of cost-effectiveness of the transition from existing one-pipe, unregulated heating systems to two-pipe regulated apartment systems, with the possibility of installing thermostatic controls on each heater as well as heat meters in each apartment. Four residential buildings with the same specific heat load, which have central regulation, group regulation, local regulation and combined regulation, were selected. The actual heat consumption has been analysed and conclusions drawn as to the possible savings with combined control. One of the main conclusions is that renovation of existing in-house heating systems is an objective necessity
Keywords: heat supply system; heating system; control valves; heat meter